Composite heat dissipation structure and electronic device using the composite heat dissipation structure
By adopting a composite heat dissipation structure in electronic products, including a metal layer, a two-layer heat dissipation coating and a hydrogen-free diamond film layer, the problem of insufficient thermal conductivity in the prior art is solved, better heat dissipation effect and structural stability are achieved, and the service life of electronic products is extended.
Patent Information
- Application Number
- CN202411554105.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The thermal conductivity of the existing electronic products is insufficient, resulting in poor heat dissipation and heat homogenization effects, poor mechanical properties and weather resistance, prone to failure, affecting the user experience and life of electronic products.
A composite heat dissipation structure is adopted, including a metal layer arranged in sequence, a first heat dissipation coating and a second heat dissipation coating. The first heat dissipation coating consists of graphene, layered alumina, carbon nanotubes and nanodiamond particles. The second heat dissipation coating consists of graphene, layered alumina, carbon nanotubes and microdiamond particles. It combines phenolic epoxy resin and epoxy resin as the adhesive member, and a hydrogen-free diamond film layer is provided on the second heat dissipation coating as the protective layer.
It improves the heat dissipation performance of electronic products, enhances the stability and thermal conductivity of the composite heat dissipation structure, reduces the risk of peeling and peeling between layers, and improves the service life and performance of electronic products.
Smart Images

Figure CN119072094B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat dissipation of electronic components, and in particular to a composite heat dissipation structure and an electronic device using the composite heat dissipation structure. Background Art
[0002] With the continuous evolution of chip manufacturing technology for flat display components and devices such as mobile phones, smart watches, tablets, laptops, and servers, the integration and multi-functionality of electronic product components are becoming increasingly higher, and the processing performance of the motherboard is also being continuously improved. In order to prevent the main core electronic components such as motherboards and chips from overheating and affecting the performance and battery life of electronic products, heat dissipation has become a key demand and function for electronic products.
[0003] In order to avoid overheating of electronic products, a heat dissipation structure is provided in the prior art to dissipate the heat generated during the use of electronic products by means of heat conduction, heat convection and heat radiation. Common heat dissipation structures include air cooling (heat dissipation fins and fans), liquid cooling (liquid and pump), heat pipes, heat dissipation films and other structures, and the above heat dissipation structures are usually unable to change their shape and structure, and cannot be adaptively adjusted according to the shape of the heat source to achieve better heat dissipation. Public patent CN116249307A discloses a heat dissipation structure and an electronic device, including a metal layer, a first adhesive layer, and a heat dissipation protective layer (including a polymer material layer and a heat dissipation coating) stacked in sequence. The heat dissipation coating includes a filler and an adhesive, and the filler is mixed in the adhesive. The filler includes graphene, carbon nanotubes, boron nitride, silicon nitride, aluminum nitride, ceramic nitride, etc. The first adhesive layer is a double-sided adhesive or a thermally conductive double-sided adhesive. The heat dissipation structure of this patent has many layers, and the layer materials include a polymer layer, an adhesive layer and a heat dissipation coating composed of adhesives. The complexity of the layer structure easily leads to unstable adhesion performance between layers. The use of polymer materials, double-sided tapes and adhesives in the heat dissipation layer materials also leads to insufficient thermal conductivity and heat dissipation performance of the heat dissipation structure.
[0004] Therefore, the heat dissipation materials of electronic product components in the prior art have low thermal conductivity, resulting in poor heat dissipation and heat distribution effects, poor mechanical properties and weather resistance, and are prone to failure during long-term use of electronic products, affecting the user experience and life of the electronic products.
[0005] Therefore, there is a need for a solution to solve the technical problems existing in the prior art. Summary of the invention
[0006] The present invention provides a composite heat dissipation structure and an electronic device using the composite heat dissipation structure, which can at least solve some of the problems existing in the prior art.
[0007] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0008] A composite heat dissipation structure, wherein the composite heat dissipation structure comprises a metal layer, a first heat dissipation coating layer, and a second heat dissipation coating layer stacked in sequence;
[0009] The first heat dissipation coating comprises a first adhesive member and a first filling member, wherein the first filling member is composed of graphene, layered aluminum oxide, carbon nanotubes and nano-diamond particles;
[0010] The second heat dissipation coating layer includes a second adhesive member and a second filling member, wherein the second filling member is composed of graphene, layered aluminum oxide, carbon nanotubes and micron diamond particles.
[0011] As a preferred solution of the composite heat dissipation structure described in the present invention, the composite heat dissipation structure further includes a protective layer arranged on the second heat dissipation coating layer, and the protective layer is a hydrogen-free diamond-like carbon film layer.
[0012] As a preferred solution of the composite heat dissipation structure described in the present invention, the thickness of the metal layer is 10-30 microns, the thickness of the first heat dissipation coating is 20-60 microns, the thickness of the second heat dissipation coating is 10-20 microns, and the thickness of the protective layer is 10-20 microns.
[0013] As a preferred solution of the composite heat dissipation structure described in the present invention, the material of the metal layer is selected from at least one of copper, aluminum, copper alloy and aluminum alloy.
[0014] As a preferred embodiment of the composite heat dissipation structure of the present invention, the first heat dissipation coating for preparing the first heat dissipation coating comprises, by weight percentage, 40-50% of a first adhesive, 5%-20% of a first filler, 0.1-0.5% of a defoamer, 0.1-0.5% of a leveling agent, 0.5-1% of a thickener, 5-10% of a curing agent, and 20-30% of a solvent;
[0015] In terms of weight percentage, the second heat dissipation coating for preparing the second heat dissipation coating includes: 50-60% second adhesive, 10%-20% second filler, 0.1-0.5% defoamer, 0.1-0.5% leveling agent, 1-2% thickener, 5-10% curing agent, and 20-30% solvent.
[0016] As a preferred embodiment of the composite heat dissipation structure of the present invention, the first filler is composed of 40-60% graphene, 10-20% layered aluminum oxide, 10-20% carbon nanotubes, and 5-10% nano-diamond particles in terms of weight percentage;
[0017] In terms of weight percentage, the second filler comprises: 30-50% graphene, 10-20% layered aluminum oxide, 10-20% carbon nanotubes, and 10-20% micron diamond particles.
[0018] As a preferred solution of the composite heat dissipation structure described in the present invention, the first adhesive member is phenolic epoxy resin, and the second adhesive member is epoxy resin.
[0019] As a preferred solution of the composite heat dissipation structure described in the present invention, the particle size of the nano diamond particles is 10-20 nanometers, and the particle size of the micro diamond particles is 10-20 micrometers.
[0020] As a preferred solution of the composite heat dissipation structure described in the present invention, the layered aluminum oxide is pre-treated with a silane coupling agent KH560 for surface modification, and the carbon nanotubes are pre-treated with a sodium dodecyl sulfate for surface modification.
[0021] As a preferred embodiment of the composite heat dissipation structure described in the present invention, the preparation method of the first heat dissipation coating comprises the following steps: dispersing and dissolving the first adhesive in a solvent under stirring, then stirring and adding a defoamer, a leveling agent, a thickener and a curing agent until they are completely dissolved, and finally adding a first filler under ultrasonic stirring until it is completely evenly dispersed, and adding an appropriate amount of deionized water to adjust the viscosity to obtain the first heat dissipation coating;
[0022] The preparation method of the second heat dissipation coating comprises the following steps: dispersing and dissolving the second adhesive in a solvent under stirring, then adding a defoamer, a leveling agent, a thickener and a curing agent under stirring until they are completely dissolved, and finally adding a second filler under ultrasonic stirring until it is completely evenly dispersed, adding an appropriate amount of deionized water to adjust the viscosity, and obtaining the second heat dissipation coating.
[0023] As a preferred solution of the composite heat dissipation structure described in the present invention, the composite heat dissipation structure has at least one through hole penetrating the composite heat dissipation structure.
[0024] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0025] An electronic device, wherein the electronic device comprises an electronic component and any one of the composite heat dissipation structures described above, and the composite heat dissipation structure is in contact with the electronic component.
[0026] The beneficial effects of the present invention are as follows:
[0027] 1. Compared with the heat dissipation structure disclosed in the prior art, the composite heat dissipation structure provided by the present invention has a simpler layer structure. The complex heat dissipation structure of the present invention includes a metal layer, a resin heat dissipation layer and a diamond-like film layer. The layer structure is relatively simpler, and the adhesive layer and polymer material layer in the prior art are not used. The simpler layer structure reduces the risk of insufficient bonding strength between layers and peeling. The adhesive layer and the polymer material layer themselves use resin and polymer materials, resulting in poor heat transfer in the heat dissipation structure, which is not conducive to the heat dissipation of electronic products. The composite heat dissipation structure of the present invention abandons the adhesive layer and the polymer material layer, and only uses a metal layer, a heat dissipation coating and a diamond-like film layer with very good thermal conductivity, which greatly improves the heat dissipation performance of the composite heat dissipation structure for electronic products.
[0028] 2. The composite heat dissipation structure provided by the present invention does not use the combination of the polymer material layer and the heat dissipation coating in the prior art, but uses two layers of heat dissipation coating. In addition to protecting the lower metal layer, the two layers of heat dissipation coating have similar compositions, making it easier for the two layers of heat dissipation coating to be bonded and attached. Compared with the combination of the polymer material layer and the heat dissipation coating, the bonding strength is higher, and the heat dissipation performance of the two layers of heat dissipation coating is also better than the combination of the polymer material layer and the heat dissipation coating. Among the two layers of heat dissipation coating, the first heat dissipation coating in contact with the metal layer uses phenolic epoxy resin, which improves the heat resistance of the heat dissipation coating as a whole. More importantly, compared with ordinary epoxy resin, the bonding strength between the phenolic epoxy resin and the metal layer is better, which improves the overall stability of the composite heat dissipation structure.
[0029] 3. The composite heat dissipation structure provided by the present invention has two layers of heat dissipation coatings, in addition to graphene, alumina, and carbon nanotubes, which are commonly used high thermal conductivity materials in the heat dissipation field, and diamond particles of different particle sizes are added to the two layers of heat dissipation coatings. Diamond has very excellent heat transfer and thermal conductivity properties, and the addition of diamond particles greatly improves the thermal conductivity and heat dissipation performance of the heat dissipation coating. In addition, the diamond particles added to the two layers of heat dissipation coatings cooperate with the thickness of the heat dissipation coating and the diamond-like film layer, thereby improving the bonding strength of the diamond-like film layer.
[0030] 4. In the composite heat dissipation structure provided by the present invention, the aluminum oxide added to the two layers of heat dissipation coating is a layered structure. The ultrasonic vibration during the mixing process increases the spacing between the layered aluminum oxide flaky layers, allowing the diamond powder particles to enter between the flaky layers, thereby enhancing the contact heat transfer effect between different thermally conductive fillers and the stability of the dispersion of diamond powder particles in the heat dissipation coating, thereby improving the overall uniformity and heat dissipation performance of the heat dissipation coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0032] Figure 1 This is a schematic diagram of a composite heat dissipation structure according to Embodiment 1 of the present invention;
[0033] Figure 2 This is a schematic diagram of a composite heat dissipation structure according to Embodiment 2 of the present invention;
[0034] Figure 3 This is a schematic diagram of the composite heat dissipation structure of Example 3 of the present invention.
[0035] Description of Figure Numbers:
[0036] 1-metal layer, 2-heat dissipation coating, 21-first heat dissipation coating, 22-second heat dissipation coating, 3-protective layer, 4-through hole.
[0037] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0038] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0040] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0041] The present invention provides a composite heat dissipation structure and an electronic device using the composite heat dissipation structure, which overcomes the defects of the prior art heat dissipation structure, i.e., poor heat conduction and heat dissipation performance of electronic components and unstable heat dissipation structure, can improve the heat dissipation performance of electronic devices, and can be applied to a variety of electronic devices, such as mobile phones, tablet computers, laptop computers, light-emitting devices, lighting devices, and other devices whose internal electronic components generate waste heat during operation. Electronic components include, but are not limited to, batteries, control chips (such as central control unit CPU), driver chips, image processors, memory (such as but not limited to SSD, solid-state hard disk), motherboards, graphics cards, display panels, light-emitting components (such as LEDs), light-emitting modules or lighting modules, or other components, units or modules that generate heat.
[0042] A composite heat dissipation structure, wherein the composite heat dissipation structure comprises a metal layer, a first heat dissipation coating layer, and a second heat dissipation coating layer stacked in sequence;
[0043] The first heat dissipation coating comprises a first adhesive member and a first filling member, wherein the first filling member is composed of graphene, layered aluminum oxide, carbon nanotubes and nano-diamond particles;
[0044] The second heat dissipation coating layer includes a second adhesive member and a second filling member, wherein the second filling member is composed of graphene, layered aluminum oxide, carbon nanotubes and micron diamond particles.
[0045] Preferably, the composite heat dissipation structure further comprises a protective layer disposed on the second heat dissipation coating layer, and the protective layer is a hydrogen-free diamond-like carbon film layer.
[0046] Preferably, the thickness of the metal layer is 10-30 microns, the thickness of the first heat dissipation coating is 20-60 microns, the thickness of the second heat dissipation coating is 10-20 microns, and the thickness of the protective layer is 10-20 microns.
[0047] Preferably, the material of the metal layer is selected from at least one of copper, aluminum, copper alloy and aluminum alloy.
[0048] The metal layer includes a metal sheet, metal foil, metal layer or metal film with high thermal conductivity, and its material may be, for example but not limited to, copper, aluminum, copper alloy (alloy of copper and other metals), aluminum alloy (alloy of aluminum and other metals) or a combination thereof. Preferably, the metal layer is copper foil.
[0049] The surface of the metal layer can be pretreated before coating the first heat dissipation coating to prepare the first heat dissipation coating. Suitable pretreatment steps include degreasing, surface roughening, etc. The surface roughening includes but is not limited to pickling, ion bombardment, polishing and other treatments of the metal layer.
[0050] Preferably, the first heat dissipation coating for preparing the first heat dissipation coating comprises, by weight percentage: 40-50% of a first adhesive, 5%-20% of a first filler, 0.1-0.5% of a defoamer, 0.1-0.5% of a leveling agent, 0.5-1% of a thickener, 5-10% of a curing agent, and 20-30% of a solvent;
[0051] In terms of weight percentage, the second heat dissipation coating for preparing the second heat dissipation coating includes: 50-60% second adhesive, 10%-20% second filler, 0.1-0.5% defoamer, 0.1-0.5% leveling agent, 1-2% thickener, 5-10% curing agent, and 20-30% solvent.
[0052] There is no clear limitation on the defoamer, leveling agent, thickener and curing agent in the heat dissipation coating, and the commonly used reagents in the field can be used. The defoamer can reduce or eliminate the bubbles generated during the mixing and dispersion process of the coating, and avoid the presence of bubbles in the applied coating, which affects the thermal conductivity and heat dissipation performance of the heat dissipation coating. The leveling agent can reduce the surface tension of the coating, increase the wettability of the coating, and enable the coating to form a flat, smooth and uniform coating during the drying and film forming process. The thickener can increase the uniform dispersion performance of the coating and prevent the sedimentation of the filler in the coating, especially the added diamond powder particles. The curing agent can increase the cross-linking density of the coating, thereby enhancing the adhesion, hardness and chemical resistance of the heat dissipation coating. The solvent can be an aqueous and / or oily solvent. The present invention preferably uses a mixed solvent of water and an organic solvent. The organic solvent that can be used is selected from ethanol, toluene, acetone, and ethyl acetate.
[0053] Regarding the specific coating method of the heat dissipation coating, the specific coating method includes but is not limited to spray coating, spin coating or precision coating.
[0054] Preferably, the first filler comprises, by weight percentage, 40-60% graphene, 10-20% layered aluminum oxide, 10-20% carbon nanotubes, and 5-10% nano-diamond particles;
[0055] In terms of weight percentage, the second filler comprises: 30-50% graphene, 10-20% layered aluminum oxide, 10-20% carbon nanotubes, and 10-20% micron diamond particles.
[0056] The filler of the present invention contains graphene, layered alumina, carbon nanotubes and diamond powder particles. By mixing fillers of different dimensions, it can be effectively stacked to form a three-dimensional heat conduction channel, enhance heat radiation and heat exchange, and enable the waste heat generated by the electronic device to be quickly transferred to the surface of the composite heat dissipation structure, thereby improving the efficiency of heat conduction and heat dissipation.
[0057] The sheet diameter (D50) of graphene can be between 1μm and 30μm, and the thickness can be between 1nm and 70nm; the diameter of carbon nanotubes can be between 5nm and 30nm, and the length can be between 5μm and 30μm. Layered alumina has a layered mesoporous structure. During ultrasonic stirring, the gap between the layers of layered alumina increases, which is conducive to the diamond powder particles in the heat dissipation coating entering the interlayer of the layered alumina, so that the diamond powder particles can be evenly and stably present in the heat dissipation coating, avoiding the sedimentation of the diamond powder particles, and improving the stability of the heat dissipation coating and the prepared heat dissipation coating. At the same time, the diamond powder particles filled in the interlayer of the layered alumina are in direct contact with the layered alumina, which improves the efficiency of heat transfer between the filling parts.
[0058] Preferably, the first adhesive is phenolic epoxy resin, and the second adhesive is epoxy resin.
[0059] The first adhesive in the first heat dissipation coating preferably uses phenolic epoxy resin. Due to its special molecular structure, phenolic epoxy resin can form a strong chemical bond with the surface of the metal substrate, which is conducive to the bonding and attachment of the composite heat dissipation structure. In addition, phenolic epoxy resin also has good chemical resistance, heat resistance and mechanical properties, which is also conducive to improving the thermal stability, physical and chemical stability of the composite heat dissipation structure.
[0060] The type of the binder in the second heat dissipating paint is not particularly limited, and bisphenol A epoxy resin is preferred.
[0061] Preferably, the particle size of the nano-diamond particles is 10-20 nanometers, and the particle size of the micro-diamond particles is 10-20 micrometers.
[0062] The nano-diamond powder particles added to the first heat dissipation coating have similar properties to the micron diamond powder particles added to the second heat dissipation coating, which is beneficial to improving the bonding strength between the first heat dissipation coating and the second heat dissipation coating. Diamond itself has a very excellent thermal conductivity coefficient. When nano-diamond powder particles are added to the first heat dissipation coating, the nano-scale powder particles can be more evenly dispersed in the heat dissipation coating to form a more continuous filler stacking structure, which helps the heat generated by the electronic device to be absorbed and transferred more quickly and evenly. At the same time, the use of nano-scale powder particles is also beneficial to the bonding and adhesion of the first heat dissipation coating and the metal layer. When micron diamond powder particles are added to the second heat dissipation coating, the micron diamond powder particles not only absorb and transfer the heat in the first heat dissipation coating, but also, because the powder particle size of the micron diamond powder particles is 10-20 microns, the micron diamond powder particles suspended in the second heat dissipation coating can be partially exposed on the surface of the prepared second heat dissipation coating to form a certain convex structure. The convex structure can, on the one hand, serve as the nucleation crystal of the subsequent protective layer diamond-like film layer, and on the other hand, the rough surface formed by the convex structure can be used to improve the bonding strength between the diamond-like film layer and the second heat dissipation structure, and enhance the structural stability of the composite heat dissipation structure.
[0063] The protective layer is a hydrogen-free diamond-like carbon film. The deposition method of the protective layer is not particularly limited. Conventional physical vapor deposition methods and chemical vapor deposition methods can be selected. Among the physical vapor deposition methods, sputtering is preferred. 3 The proportion of hybrid structure atoms is not less than 70%, sp 3 The hybrid structure of diamond-like carbon has excellent thermal conductivity, has good thermal conductivity in both the lateral and longitudinal directions, and can maintain good bonding strength and mechanical strength under alternating conditions of high and low temperatures. 3 The hybrid structure of diamond-like carbon has high hardness, good corrosion resistance, and excellent tribological properties. It is used as a protective layer in the outermost layer of the composite heat dissipation structure. It can improve the mechanical properties, chemical corrosion resistance and wear resistance of the heat dissipation structure while improving the thermal conductivity.
[0064] Preferably, the layered aluminum oxide is preliminarily subjected to surface modification treatment using a silane coupling agent KH560, and the carbon nanotubes are preliminarily subjected to surface modification treatment using sodium dodecyl sulfate.
[0065] Pre-treating the layered alumina with a silane coupling agent and pre-treating the carbon nanotubes with sodium dodecyl sulfate can improve the surface activity of the layered alumina and the carbon nanotubes, avoid agglomeration and sedimentation of the layered alumina and the carbon nanotubes in the heat dissipation coating, and improve the stability of the heat dissipation coating and the uniformity of the heat dissipation coating.
[0066] Preferably, the preparation method of the first heat dissipation coating comprises the following steps: dispersing and dissolving the first adhesive in a solvent under stirring, then stirring and adding a defoamer, a leveling agent, a thickener and a curing agent until they are completely dissolved, and finally adding a first filler under ultrasonic stirring until it is completely evenly dispersed, and adding an appropriate amount of deionized water to adjust the viscosity to obtain the first heat dissipation coating;
[0067] The preparation method of the second heat dissipation coating comprises the following steps: dispersing and dissolving the second adhesive in a solvent under stirring, then adding a defoamer, a leveling agent, a thickener and a curing agent under stirring until they are completely dissolved, and finally adding a second filler under ultrasonic stirring until it is completely evenly dispersed, adding an appropriate amount of deionized water to adjust the viscosity, and obtaining the second heat dissipation coating.
[0068] Preferably, the composite heat dissipation structure has at least one through hole penetrating the composite heat dissipation structure.
[0069] The composite heat dissipation structure can be processed to have multiple through holes. When the heat source of the electronic device is attached to the composite heat dissipation structure, the through holes can prevent the air in the gap between the two from expanding due to heat, causing the composite heat dissipation structure and the heat source to separate. The hot air is discharged through the through holes, thereby avoiding deformation of the heat dissipation structure or even separation from the heat source.
[0070] An electronic device, wherein the electronic device comprises an electronic component and any one of the composite heat dissipation structures described above, and the composite heat dissipation structure is in contact with the electronic component.
[0071] The electronic device may be, for example but not limited to, a flat panel display, a light emitting device or an illumination device, such as but not limited to a mobile phone, a laptop computer, a tablet computer, a television, a display, a backlight module, a light emitting or illumination device, or other electronic devices. The heat source may be a battery, a control chip (such as a central control unit (CPU)), a driver chip, an image processor, a memory (such as but not limited to an SSD, solid state drive), a motherboard, a graphics card, a display panel, a light emitting or illumination module with a light emitting diode, or other components, modules or units that generate high heat, without limitation.
[0072] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.
[0073] Example 1
[0074] Combination Figure 1 As shown, a composite heat dissipation structure includes a metal layer 1, a first heat dissipation coating 21, and a second heat dissipation coating 22 which are stacked in sequence. The first heat dissipation coating 21 and the second heat dissipation coating 22 together constitute a heat dissipation coating.
[0075] The material of the metal layer 1 is copper foil with a thickness of 12 micrometers. Before coating the first coating, the copper foil is pretreated by ion bombardment.
[0076] The first heat dissipation coating 21 is prepared by spraying and has a thickness of 50 microns. The first heat dissipation coating used is composed of the following by weight percentage: 45% first adhesive, 15% first filler, 0.5% defoamer, 0.5% leveling agent, 1% thickener, 8% curing agent, and 30% solvent. Figure 1 Only the first filling member is schematically shown in FIG. 1 , and the embedding of the nano-diamond particles in the layered aluminum oxide is not shown.
[0077] The material of the first bonding member is phenolic epoxy resin F-51, and the solvent is deionized water and ethanol in a volume ratio of 1:1.
[0078] The first filler is composed of 60% graphene, 20% layered aluminum oxide, 10% carbon nanotubes, and 10% nano-diamond particles in terms of mass percentage. The nano-diamond particles have a particle size range of 10-20 nanometers after screening.
[0079] The second heat dissipation coating 22 is prepared by spraying and has a thickness of 15 microns. The second heat dissipation coating used is composed of the following by weight percentage: 50% second adhesive, 10% second filler, 0.5% defoamer, 0.5% leveling agent, 2% thickener, 7% curing agent, and 30% solvent. Figure 1 Only the distribution of the micron diamond particles in the second filler is schematically shown, and the distribution of other components in the second filler is not shown.
[0080] The material of the second adhesive is epoxy resin E51, and the solvent is deionized water and ethanol in a volume ratio of 1:1.
[0081] The second filler is composed of 50% graphene, 20% layered aluminum oxide, 15% carbon nanotubes, and 15% micron diamond particles in terms of mass percentage. The micron diamond particles have a particle size range of 10-20 microns after screening.
[0082] Example 2
[0083] Combination Figure 2 As shown, the structure and composition of the metal layer and the heat dissipation coating are the same as those of Example 2, except that the composite heat dissipation structure prepared in Example 2 also includes a protective layer 3 arranged on the surface of the second heat dissipation coating 22.
[0084] The protective layer 3 is a hydrogen-free diamond-like carbon film layer with a thickness of 10 microns. The protective layer 3 is prepared by magnetron sputtering, using graphite high sputtering target and argon as process gas to obtain a high sp 3 The thickness of the hydrogen-free diamond-like carbon film layer with hybrid structure is 15 microns.
[0085] Example 3
[0086] Combination Figure 3 As shown, the structure and composition of each layer are the same as those of Example 2, except that a plurality of through holes 4 penetrating the composite heat dissipation structure are processed and arranged in the composite heat dissipation structure prepared in Example 3.
[0087] Comparative Example 1
[0088] Take the heat dissipation structure and the electronic device structure of the embodiment in the Chinese patent application with publication number CN116249307A as an example.
[0089] Comparative Example 2
[0090] The structure and composition of each layer are the same as those of Example 2, except that no layered alumina is added to the first heat dissipation coating and the second heat dissipation coating, but spherical alumina particles are added, and the particle size of the alumina particles ranges from 30 to 40 microns.
[0091] Comparative Example 3
[0092] The difference from Example 2 is that only one layer of heat dissipation coating is applied, and the heat dissipation coating is formed by spraying the first heat dissipation coating. The thickness of the heat dissipation coating is the sum of the thickness of the first heat dissipation coating and the second heat dissipation coating in Example 2, which is 65 microns in total.
[0093] Comparative Example 4
[0094] The difference from Example 2 is that only one layer of heat dissipation coating is applied, and the heat dissipation coating is formed by spraying the second heat dissipation coating. The thickness of the heat dissipation coating is the sum of the thickness of the first heat dissipation coating and the second heat dissipation coating in Example 2, which is 65 microns in total.
[0095] The heat dissipation performance, hardness, corrosion resistance, high temperature resistance and impact energy of the heat dissipation structures obtained in Example 2 and Comparative Examples 1-4 were tested. The specific test methods and test results are as follows:
[0096] Heat dissipation performance test: each heat dissipation structure sample and heat source were cut into the same size of 50mm×50mm, and each heat dissipation structure sample was attached to the surface of the heat source using the same conductive double-sided tape. The heat source temperature was set to 80℃, 90℃, and 100℃ respectively, and the temperature of the heat source after heat dissipation by the heat dissipation structure was measured. The test results are shown in Table 1.
[0097] Adhesion test: According to GB / T 9286-98, the adhesion of each sample was tested using a 100-grid tester. The test results are shown in Table 2.
[0098] Hardness test: The hardness of each sample was tested according to the coating hardness pencil test method of GB / T6739-1996. The test results are shown in Table 2.
[0099] Corrosion resistance test: The corrosion resistance test is carried out by salt spray aging test. The specific test standard is GB1865-2009. The test results are shown in Table 2.
[0100] High temperature impact resistance test: The prepared heat dissipation structures with heat sources were placed in an environment of 100°C for 1.0 h, and then quickly cooled. The above insulation and cooling steps were repeated 500 times. Finally, the thermal conductivity of the heat dissipation structure was observed compared with the thermal conductivity of the sample before the test. The test results are shown in Table 2.
[0101] Table 1
[0102]
[0103] It can be seen from the heat dissipation test results of the heat dissipation structures of each sample that the composite heat dissipation structure of the present invention has very good heat conduction and heat dissipation effects for different heat sources, and the cooling effect for 80℃, 90℃, and 100℃ heat sources can reach 19.7℃ to 21.6℃. In contrast, the heat dissipation structures of the comparative examples, the heat dissipation structure in the prior art used in comparative example 1, has a cooling effect of only about 10℃, and the highest is only 12.5℃. The heat dissipation structure of comparative example 2 uses spherical alumina particles as the raw material of the filler, resulting in a significant improvement in its heat conduction and heat dissipation effect compared with comparative example 1, but it is lower than the heat dissipation effect of the present invention. The heat dissipation structure of comparative example 3 only uses the heat dissipation coating prepared by the first heat dissipation coating. Due to the small particle size of the nano-diamond powder particles, a large number of nano-particles are evenly dispersed in the heat dissipation coating, and fully contact with other components in the filler to transfer heat, so that the heat conduction and heat dissipation effect of the heat dissipation structure is excellent, and the cooling effect can reach 21.2℃ to 22.1℃. The heat dissipation structure of Comparative Example 4 only uses the heat dissipation coating prepared by the second heat dissipation coating, which also significantly improves the heat dissipation effect of the heat source compared to Comparative Example 1. However, due to the relatively large particle size of the micron diamond powder particles, it is not easy to embed into the layered alumina. At the same time, due to the relatively poor distribution uniformity in the heat dissipation coating, its thermal conductivity and heat dissipation effect is slightly lower than that of Comparative Example 3.
[0104] Table 2
[0105] Sample / Testing Adhesion hardness Corrosion resistance High temperature shock resistance Example 2 5B 9H No corrosion 97% Comparative Example 1 5B 2H Slight corrosion 87% Comparative Example 2 5B 9H No corrosion 97% Comparative Example 3 4B 9H No corrosion 94% Comparative Example 4 4B 9H No corrosion 96%
[0106] From the performance test results of the heat dissipation structures of various samples, the heat dissipation structure prepared by the present invention has excellent adhesion, hardness, corrosion resistance and high temperature impact resistance. The heat dissipation structure of the prior art adopted in Comparative Example 1, each layer of the heat dissipation structure is a double-sided adhesive or a polymer or resin film layer, and a high-hardness diamond-like film layer is not provided on the surface. Its surface hardness is much lower than the heat dissipation structure provided with a diamond-like film layer in Example 2 of the present invention and Comparative Examples 2-4. In addition, the metal layer of the bottom layer of the heat dissipation structure of Comparative Example 1 also showed slight corrosion in the salt spray test due to the lack of protection of the diamond-like film layer. The heat dissipation structure of Comparative Example 2 also has good adhesion, hardness, corrosion resistance and high temperature impact resistance. Since the heat dissipation structures of Comparative Examples 3-4 only use micron diamond powder particles or nano diamond powder particles as fillers, the diamond-like film layer in the heat dissipation structure of Comparative Example 3 lacks the anchoring effect of the micron diamond protrusions, and the adhesion of the heat dissipation structure is reduced. Although the heat dissipation structure of Comparative Example 4 has anchoring of micron diamond protrusions, micron diamond powder particles are used in the fillers, and the particles are larger, resulting in a decrease in the bonding strength between the heat dissipation coating and the metal layer.
[0107] Based on the comprehensive thermal conductivity and heat dissipation effect as well as the adhesion, hardness, corrosion resistance and high temperature impact resistance tests of the heat dissipation structure, the composite heat dissipation structure of the present invention has good stability and heat dissipation effect, and can be used in electronic devices to provide heat dissipation protection for heat sources.
[0108] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A composite heat dissipation structure, characterized in that: The composite heat dissipation structure comprises a metal layer, a first heat dissipation coating, a second heat dissipation coating, and a hydrogen-free diamond-like film protective layer which are stacked in sequence; The first heat dissipation coating includes a first adhesive and a first filler, the first adhesive is a phenolic epoxy resin, and the first heat dissipation coating for preparing the first heat dissipation coating includes, by weight percentage: 40-50% of the first adhesive, 5%-20% of the first filler, 0.1-0.5% of the defoamer, 0.1-0.5% of the leveling agent, 0.5-1% of the thickener, 5-10% of the curing agent, and 20-30% of the solvent; In terms of weight percentage, the first filler is composed of: 40-60% graphene, 10-20% layered aluminum oxide, 10-20% carbon nanotubes, and 5-10% nano-diamond particles, wherein the particle size of the nano-diamond particles is 10-20 nanometers, and the thickness of the first heat dissipation coating is 20-60 micrometers; The second heat dissipation coating includes a second adhesive and a second filler, the second adhesive is an epoxy resin, and the second heat dissipation coating for preparing the second heat dissipation coating includes, by weight percentage: 50-60% of the second adhesive, 10%-20% of the second filler, 0.1-0.5% of the defoamer, 0.1-0.5% of the leveling agent, 1-2% of the thickener, 5-10% of the curing agent, and 20-30% of the solvent; In terms of weight percentage, the second filler is composed of: 30-50% graphene, 10-20% layered alumina, 10-20% carbon nanotubes, and 10-20% micron diamond particles, the particle size of the micron diamond particles is 10-20 microns, and the thickness of the second heat dissipation coating is 10-20 microns.
2. A composite heat dissipation structure according to claim 1, characterized in that: The thickness of the hydrogen-free diamond-like carbon film layer is 10-20 microns.
3. A composite heat dissipation structure according to claim 2, characterized in that: The thickness of the metal layer is 10-30 microns.
4. A composite heat dissipation structure according to claim 3, characterized in that: The material of the metal layer is selected from at least one of copper, aluminum, copper alloy and aluminum alloy.
5. A composite heat dissipation structure according to claim 4, characterized in that: The layered alumina is preliminarily surface-modified using a silane coupling agent KH560, and the carbon nanotube is preliminarily surface-modified using sodium dodecyl sulfate.
6. A composite heat dissipation structure according to claim 5, characterized in that: The preparation method of the first heat dissipation coating comprises the following steps: dispersing and dissolving the first adhesive in a solvent under stirring, then stirring and adding a defoamer, a leveling agent, a thickener and a curing agent until they are completely dissolved, and finally adding a first filler under ultrasonic stirring until it is completely evenly dispersed, and adding an appropriate amount of deionized water to adjust the viscosity to obtain the first heat dissipation coating; The preparation method of the second heat dissipation coating comprises the following steps: dispersing and dissolving the second adhesive in a solvent under stirring, then adding a defoamer, a leveling agent, a thickener and a curing agent under stirring until they are completely dissolved, and finally adding a second filler under ultrasonic stirring until it is completely evenly dispersed, adding an appropriate amount of deionized water to adjust the viscosity, and obtaining the second heat dissipation coating.
7. A composite heat dissipation structure according to claim 6, characterized in that: The composite heat dissipation structure has at least one through hole penetrating the composite heat dissipation structure.
8. An electronic device, characterized in that: The electronic device comprises an electronic component and the composite heat dissipation structure according to any one of claims 1 to 7, wherein the composite heat dissipation structure is in contact with the electronic component.
Citation Information
Patent Citations
Heat dissipation structure and electronic device
CN116249307A
Heat dissipation structure
CN111961386A
Heat conduction structure and electronic device
CN114823574A
Heat dissipation structure and electronic device
TWM625594U